Alternative Approaches for the Management of Diabetic Foot Ulcers - Pouget, Cassandra; Dunyach-Remy, Catherine; Pantel, Alix; Boutet-Dubois, Adeline; Schuldiner, Sophie; Sotto, Albert; Lavigne, Jean-Philippe; Loubet, Paul (Frontiers in Microbiology, 2021)
Diabetic foot ulcers (DFU) represent a growing public health problem. The emergence of multidrug-resistant (MDR) bacteria is a complication due to the difficulties in distinguishing between infection and colonization in DFU. Another problem lies in biofilm formation on the skin surface of DFU. Biofilm is an important pathophysiology step in DFU and may contribute to healing delays. Both MDR bacteria and biofilm producing microorganism create hostile conditions to antibiotic action that lead to chronicity of the wound, followed by infection and, in the worst scenario, lower limb amputation. In this context, alternative approaches to antibiotics for the management of DFU would be very welcome. In this review, we discuss current knowledge on biofilm in DFU and we focus on some new alternative solutions for the management of these wounds, such as antibiofilm approaches that could prevent the establishment of microbial biofilms and wound chronicity. These innovative therapeutic strategies could replace or complement the classical strategy for the management of DFU to improve the healing process.